The Level Of Public Trust And Lifestyle Towards The Decision To Save In The Syariah Financing Savings And Loan Cooperative BMT Nu Jatim - Muhammad Isbad Addainuri; Nashar Nashar (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Banks or sharia financial institutions function as agents of trust, Baitul Mal Wa Tanwil (BMT) not only hopes for increased public interest in choosing BMT as a vehicle for investment and saving. Apart from that, people's lifestyle patterns also greatly influence people's savings in financial institutions. Lifestyle in general is a person's overall lifestyle expressed in activities, interests and opinions. So it can be said that people's level of trust and lifestyle greatly influence the decision to become a customer. This research aims to find out whether people's level of trust and lifestyle influence the decision to save at KSPPS BMT NU East Java, as well as analyzing which variables have the most influence on the decision to save at KSPPS BMT NU East Java. This study uses a quantitative approach with descriptive statistical analysis techniques and multiple linear regression tests using SPSS software. The data used in this research is primary data obtained from the results of a questionnaire filled out by 75 customers at KSPPS BMT NU East Java. The results of this study show that there is a simultaneous influence between the variables of trust and lifestyle on the decision to save at KSPPS BMT NU East Java. The variable that has the most dominant influence on the decision to save is the lifestyle variable, with a regression coefficient for the trust variable of 0.312, while the regression coefficient for the lifestyle variable is 0.564.